2010
DOI: 10.4319/lo.2010.55.3.1172
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability in the cycling of nitrogen within a constructed wetland: A whole‐system stable‐isotope‐addition experiment

Abstract: Constructed wetlands attenuate effluent nutrients, are hydrodynamically well defined, and are a useful proxy for the study of nitrogen (N) transformation in eutrophic natural systems. A whole-system stable-isotope addition was undertaken to describe the N cycling within a constructed wetland. Addition of 15 NH z 4 and particulate organic 15 N (PO 15 N) and a conservative tracer (Li + ) revealed that, initially, sedimentation of PO 15 N and assimilatory uptake of 15 NH z 4 near the wetland inlet removed most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Long‐term 15 N labeling studies of freshwater and marine marshes have shown the highest losses during the first month (De Laune et al ; White and Howes ; Gribsholt et al ), although our losses were much higher. For example, after one month 76% of the added 15 N remained in a salt marsh system (White and Howes ), 66% remained in a freshwater constructed wetland (Erler et al ) and 50% remained in a tidal freshwater system (Gribsholt et al ). All these studies with higher retention showed rapid transfer of 15 N into plants, which enhances the short‐term retention.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term 15 N labeling studies of freshwater and marine marshes have shown the highest losses during the first month (De Laune et al ; White and Howes ; Gribsholt et al ), although our losses were much higher. For example, after one month 76% of the added 15 N remained in a salt marsh system (White and Howes ), 66% remained in a freshwater constructed wetland (Erler et al ) and 50% remained in a tidal freshwater system (Gribsholt et al ). All these studies with higher retention showed rapid transfer of 15 N into plants, which enhances the short‐term retention.…”
Section: Discussionmentioning
confidence: 99%
“…Whole ecosystem 15 N isotope addition techniques recently refined for headwater streams (Mulholland et al 2008) could yield new insights into the processing of N in hydrologically complex aquatic ecosystems, but so far there have been only a few applications within wetlands (Tobias et al 2003;Gribsholt et al 2005;Erler et al 2010). Tracer addition experiments using 15 N have demonstrated the importance of in-stream processes (assimilation and denitrification) in reducing N export from watersheds Mulholland et al 2008).…”
mentioning
confidence: 99%
“…Blue boxes represent pre-treatment options to treat Group 1 constituents; green boxes represent primary treatment options to treat Group 2 constituents; red boxes represent secondary treatment options to treat Group 3 constituents; and grey boxes represent secondary treatment options to treat Group 4 constituents. Based on Gray (2005) and Hammer & Hammer (2008) fication and anammox pathways occurring in the sludge and NO 3 − and NH 4 + are preferentially assimilated by algae (Erler et al 2010, de Paula Silva et al 2012. Conversion from DON to dissolved inorganic nitrogen (DIN) is therefore beneficial to reducing total nitrogen (Erler et al 2010).…”
Section: Dissolved Constituentsmentioning
confidence: 99%
“…Based on Gray (2005) and Hammer & Hammer (2008) fication and anammox pathways occurring in the sludge and NO 3 − and NH 4 + are preferentially assimilated by algae (Erler et al 2010, de Paula Silva et al 2012. Conversion from DON to dissolved inorganic nitrogen (DIN) is therefore beneficial to reducing total nitrogen (Erler et al 2010).…”
Section: Dissolved Constituentsmentioning
confidence: 99%
See 1 more Smart Citation